Characterization of MADS-Box Gene Family in Isatis indigotica and Functional Study of IiAP1 in Regulating Floral Transition and Formation - Yanqin Ma; Yanhong Lan; Ju Li; Haicheng Long; Yujie Zhou; Zhi Li; Mingjun Miao; Jian Zhong; Haie Wang; Wei Chang; Ziqin Xu; Liang Yang (Plants)
In flowering plants, MADS-box genes play regulatory roles in flower induction, floral initiation, and floral morphogenesis. Isatis indigotica (I. indigotica) is a traditional Chinese medicinal plant. However, available information concerning MADS-box genes in I. indigotica is insufficient. Based on the sequencing data of the I. indigotica transcriptome, we identified MADS-box gene-encoding transcription factors that have been shown to play critical roles in developmental processes. In this study, 102 I. indigotica MADS-box genes were identified and categorized into type I (Mα, Mβ, and Mγ) and type II (MIKCC and MIKC*) subfamilies. IiMADS proteins in the same cluster had similar motifs and gene structures. In total, 102 IiMADS-box genes were unevenly distributed across seven chromosomes. APETALA1 (AP1) encodes a MADS-box transcription factor which plays a pivotal role in determining floral meristem identity and also modulates developmental processes within the perianth. We then selected IiAP1 for functional studies and found that it is localized to the nucleus and highly expressed in inflorescence, sepals, and petals. The ectopic expression of IiAP1 in Arabidopsis resulted in early flowering and abnormal development of floral organs. Taken together, this research study carried out a systematic identification of MADS-box genes in I. indigotica and demonstrated that IiAP1 takes part in the regulation of floral transition and formation.